Environmental sustainability in Sub-Saharan Africa: Does information and communication technology (ICT) matter? - Mamadou Asngar Thierry; Ongo Nkoa Bruno Emmanuel; Nchofua Protus Biondeh (Cogent Economics & Finance, 2022)
This study investigates the effect of information and communication technology (ICT) on environmental sustainability in 38 Sub-Saharan African (SSA) countries over a period 2000-2016. ICT is measured by internet penetration and mobile phone penetration whereas environmental sustainability is measured by CO2 emissions. The empirical evidence is based on the extended stochastic impact by regression on population, affluence and technology model. As estimation techniques, pooled ordinary least squares (OLS), fixed effect (FE), random effect (RE), panel correlated standard error (PCSE) and feasible generalised least squares (FGLS) are employed. The finding broadly shows that investment in ICT infrastructure enhances environmental sustainability. In addition, the effect of ICT is uniform across different income levels in SSA. As a policy implication, universal ICT access that encourages low pricing and broad coverage of equipment should be considered.
Keywords: 330; CO2 emissions; environmental sustainability; ICT; Sub-Saharan Africa